Cross-year peer tutoring on internal medicine wards: results of a qualitative focus group analysis - Krautter, Markus (Dove Medical Press, 2014)
BACKGROUND: Peer-assisted learning (PAL) has become a well-accepted teaching method within medical education. However, descriptions of on-ward PAL programs are rare. A focus group analysis of a newly established PAL program on an internal medicine ward was conducted to provide insights into PAL teaching from a student perspective. PURPOSE: To provide insights into students’ experiences regarding their on-ward training with and without accompanying PAL tutors. METHODS: A total of N=168 medical students in their sixth semester participated in the investigation (intervention group: N=88; control group: N=80). The intervention group took part in the PAL program, while the control group received standard on-ward training. There were seven focus groups with N=43 participants (intervention group: four focus groups, N=28 participants; control group: three focus groups, N=15 participants). The discussions were analyzed using content analysis. RESULTS: The intervention group emphasized the role of the tutors as competent and well-trained teachers, most beneficial in supervising clinical skills. Tutors motivate students, help them to integrate into the ward team, and provide a non-fear-based working relationship whereby students’ anxiety regarding working on ward decreases. The control group had to rely on autodidactic learning strategies when neither supervising physicians nor final-year students were available. CONCLUSION: On-ward PAL programs represent a particularly valuable tool for students’ support in training clinical competencies on ward. The tutor–student working alliance acts through its flat hierarchy. Nevertheless, tutors cannot represent an adequate substitute for experienced physicians.